Exploring Kindergarten Learners’ Environmental Consciousness through Drawings: Towards Instructional Materials Development - Batchar, Rendel; Abad, Glenda; Tigas, Blessilda Grace; Farro, Rosemarie; Corintin, Mark Anthony (Papanda Publisher, 2025)
Global environmental crises pose significant challenges to achieving sustainable development, making it imperative to integrate environmental awareness into education at all levels. Early childhood, particularly the kindergarten stage, is a crucial period for cultivating environmental consciousness and instilling lifelong sustainable values. Despite its importance, research on early childhood environmental education (ECEE) in the Philippines remains limited, leaving a gap in understanding how young learners perceive and engage with their environment. This study sought to address this gap by exploring the environmental consciousness of 39 kindergarten pupils at a laboratory school in Central Luzon, Philippines. Using the draw-and-tell technique, combined with semiotic analysis, it examined both the visual and verbal expressions of these young learners. Pupils' drawings featured natural elements (flowers, trees, clouds, and the sun), representations of biodiversity (birds and animals), and the built environment (houses). Imaginative features, such as balloons and rainbows, showcased their creative interpretations of the environment. Oral narratives complemented the drawings, offering deeper insights into their perspectives on environmental issues. The findings underscore the potential of ECEE to nurture environmentally responsible behavior from an early age and inform the creation of green instructional resources, including storybooks designed specifically for kindergarten learners.